Dispersed Manufacturing Networks Challenges for Research and Practice - Dekkers, Rob (Springer London : Imprint: Springer, 2009)
Customers in geographically dispersed, emerging and established global markets nowadays demand higher quality products in a greater variety, at lower cost, and in a shorter time. As a result, organizations have moved from centralized, vertically integrated, single-site manufacturing facilities to geographically dispersed networks of resources. The emerging possibilities of information technology and data communication, the globalization of markets, and the ongoing specialization of firms have paved the way for Dispersed Manufacturing Networks as an organizational paradigm for collaboration and coordination across loosely connected agents. Dispersed Manufacturing Networks provides new perspectives of dispersed manufacturing systems from three points of view. The first is that offered by complex systems theory, particularly on how agents in these industrial networks interact and how that provides possibility for coordination. The book also elaborates on issues of coordination and planning, as well as examining new solutions and challenges for logistics problems and collaboration in engineering networks within the internationalisation perspective. These methods and tools offer pathways to the development of integrative approaches. The impact of globalization is discussed for both managerial decision-making and operational performance of supply chains. A strong emphasis is placed on the need for continuous decision-making with recognition of the fact that networks of loosely connected agents require different approaches. Both researchers and professionals will welcome Dispersed Manufacturing Networks. It is an informative guide for those researching and working across a range of fields, including manufacturing management and networks; ICT applications, such as virtual networks or holonic manufacturing; and operations management.